Approaches About Emotions and Feelings in Research with Wheelchair Users: A Review - de Sousa Chaparro, Marianna [UNESP]; de Oliveira, Paula C. R. [UNESP]; Medola, Fausto Orsi [UNESP]; Paschoarelli, Luis Carlos [UNESP] (Springer Nature, 2022)
The present review sought to raise discussions about how emotions and feelings are addressed in research with users of manual wheelchairs. Although there is a small amount of specialized research in this field, it was possible to list 6 aspects to be discussed: main emotions and feelings, perception of emotions and feelings by the user, social and family influences, influences from rehabilitation and leisure programs, protocols and methods reported, relationship with the wheelchair and with their disabilities. As a conclusion of this discussion: there was an influence of external and internal factors on emotions and feelings, the time of using the wheelchair, the age and gender of the users of the technology. Indirectly, it was concluded that more robust studies are still needed on the emotions and feelings involved in the relationship between user, artifact and daily activities in the field of product design, with the aim of improving interaction with the technological physical interfaces.
Keywords: Assistive technology; Emotions; Wheelchair users